2014
DOI: 10.1093/carcin/bgu092
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate susceptibility genes for colorectal cancer through eQTL analysis

Abstract: In this study, we aim to identify the genes responsible for colorectal cancer risk behind the loci identified in genome-wide association studies (GWAS). These genes may be candidate targets for developing new strategies for prevention or therapy. We analyzed the association of genotypes for 26 GWAS single nucleotide polymorphisms (SNPs) with the expression of genes within a 2 Mb region (cis-eQTLs). Affymetrix Human Genome U219 expression arrays were used to assess gene expression in two series of samples, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 45 publications
5
55
0
Order By: Relevance
“…From statistical results, different SNPs could relate to different target genes. This situation could be explained by remote regulation among related genes, and is common in many other studies [32][33][34]. For example, Weinhold et al [32] conducted eQTL analysis and found that at 7p15.3 the strongest association with multiple myeloma risk was for rs4487645, residing within the DNAH11 gene, which was associated with allele-specific regulation of the CDCA7L gene (near the DNAH11 gene).…”
Section: Discussionmentioning
confidence: 92%
“…From statistical results, different SNPs could relate to different target genes. This situation could be explained by remote regulation among related genes, and is common in many other studies [32][33][34]. For example, Weinhold et al [32] conducted eQTL analysis and found that at 7p15.3 the strongest association with multiple myeloma risk was for rs4487645, residing within the DNAH11 gene, which was associated with allele-specific regulation of the CDCA7L gene (near the DNAH11 gene).…”
Section: Discussionmentioning
confidence: 92%
“…We identified significant regulation relations between rs9929218 variant and gene expression including CDH1, ZFP90, RP11-354M1.2 and MCOLN2 by both cis- effect and trans- effect. Recently, Closa et al analyzed the association between genotypes for 26 GWAS SNPs and the expression of genes within a 2 Mb region (cis-eQTLs) using Affymetrix Human Genome U219 expression arrays with 47 samples from healthy colonic mucosa and 97 samples from normal mucosa adjacent to colon cancer [26]. In all the samples, the cis-eQTL analysis showed significant association between rs9929218 variant and GFOD2 expression with P =3.90E-03 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Closa et al analyzed the association between genotypes for 26 GWAS SNPs and the expression of genes within a 2 Mb region (cis-eQTLs) using Affymetrix Human Genome U219 expression arrays with 47 samples from healthy colonic mucosa and 97 samples from normal mucosa adjacent to colon cancer [26]. In all the samples, the cis-eQTL analysis showed significant association between rs9929218 variant and GFOD2 expression with P =3.90E-03 [26]. Closa et al further reported significant association of rs9929218 variant with expression of TSNAXIP1, HSF4 and NUTF2 in tumor tissue eQTL analysis with P =5.50E-03, P =6.70E-03 and P =1.70E-03, respectively, but not in normal tissue eQTL analysis with P =0.59, P =0.54 and P =0.27, respectively [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations